Analisis Pengaruh Costumer Bonding Dan Brand Awareness Terhadap Kepuasan Pelanggan Natasha Skincare Cabang Malang - Innaya Tussolekha Sanggaria; Muhammad Ridwan Basalamah; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Customer Bonding and Brand Awareness on Customer Satisfaction Natasha Skincare Malang branch. the population used in this study were Natasha Skincare customers. The technique used in sampling in this study is purposive sampling. The variables in this study are Customer Bonding, Brand Awareness and Customer Satisfaction. The data collection method used in this research is a questionnaire given to customers and libraries, namely from journals and articles. The analysis used is multiple linear regression. The results of this study explain that the variable Customer Bonding and Brand Awareness, customer bonding, and brand awareness Keywords: Costumer Bonding, Brand Awareness, Customer Satisfaction